PENINGKATAN PEMBELAJARAN SERVIS BAWAH MELALUI BERMAIN LEMPAR TANGKAP DI SDN 36 SERIMBANG - T, Akim; G. Simanjuntak, Victor; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The problem in this research can be whether through plastic ball The problem of this study is whether there is an increase in service learning down through playing catch-throws on grade V students of State Elementary School 36 Serimbang Landak. The purpose of this research is to know the improvement of service learning down through playing catch-throw. The method used in this research is descriptive method with research type that is class action research. Subjects in the study were teachers collaborating with students that is as many as 30 students. The first cycle there is a result of completeness by the number of 12 students or by 40% and students who have not completed 18 students or 60%. While the second cycle there are student results with complete category with all students graduated amounted to 30 students or 100% and not complete 0 or none.Keywords: Service Â down, throwing catch